Analisis Gaya Kepemimpinan dalam Meningkatkan Motivasi Kerja Karyawan pada PT. BSI Bukittinggi Pasar Aur - Fahrila Firdaus; Sandra Dewi (Universitas 45 Surabaya, 2024)
This study aims to determine the leadership style in motivating employee work applied at PT BSI Bukittinggi Pasar Aur. The informants in this study were 3 people, namely the head of BSI Bukittinggi and 2 BSI employees, namely the marketing and customer service departments. This research is field research (field reserch) or commonly called qualitative research. The method in this research uses descriptive analysis with a qualitative approach. Based on the results of the study that (1) that the leadership style applied varies depending on the situation and characteristics of employees (2) Employees feel more motivated and productive when leaders show empathy, provide support, and involve them in decision making. Increasing employee work depends heavily on the leader's ability to apply leadership styles according to employee needs. (3) in improving employee work motivation, leaders must always ensure that the company's vision and mission must be well understood and become a reference in decision making. (4) leadership is the process of influencing in determining organisational goals, motivating several parties to achieve goals, influencing to improve the group and its culture.